2002
DOI: 10.1038/ng1047
|View full text |Cite|
|
Sign up to set email alerts
|

Functional SNPs in the lymphotoxin-α gene that are associated with susceptibility to myocardial infarction

Abstract: By means of a large-scale, case-control association study using 92,788 gene-based single-nucleotide polymorphism (SNP) markers, we identified a candidate locus on chromosome 6p21 associated with susceptibility to myocardial infarction. Subsequent linkage-disequilibrium (LD) mapping and analyses of haplotype structure showed significant associations between myocardial infarction and a single 50 kb halpotype comprised of five SNPs in LTA (encoding lymphotoxin-alpha), NFKBIL1 (encoding nuclear factor of kappa lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
647
5
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 863 publications
(678 citation statements)
references
References 23 publications
25
647
5
1
Order By: Relevance
“…136 The recent identification of the IkBL (NFKBIL1) gene as the second MHC susceptibility locus for RA with the identification of a IkBL promoter SNP (À62) as disrupting a putative binding motif for a transcription repressor 43 demonstrates that broad mapping of the MHC is a powerful strategy. Interestingly, this locus was also identified in studies of myocardial infarction 44 and breast cancer susceptibility. 156 Okazi et al 44 opted for LTA as their disease causing locus, and showed that two variants were functional in in vitro assays, which is supported by the recent identification of differential expression from LTA alleles.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…136 The recent identification of the IkBL (NFKBIL1) gene as the second MHC susceptibility locus for RA with the identification of a IkBL promoter SNP (À62) as disrupting a putative binding motif for a transcription repressor 43 demonstrates that broad mapping of the MHC is a powerful strategy. Interestingly, this locus was also identified in studies of myocardial infarction 44 and breast cancer susceptibility. 156 Okazi et al 44 opted for LTA as their disease causing locus, and showed that two variants were functional in in vitro assays, which is supported by the recent identification of differential expression from LTA alleles.…”
Section: Discussionmentioning
confidence: 85%
“…Interestingly, this locus was also identified in studies of myocardial infarction 44 and breast cancer susceptibility. 156 Okazi et al 44 opted for LTA as their disease causing locus, and showed that two variants were functional in in vitro assays, which is supported by the recent identification of differential expression from LTA alleles. 198 However, they also showed that the IkBL promoter SNP (described as À63) affects promoter activity in transient transfection assays, illustrating the difficulty of clearly identifying the causative genetic lesion.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Recently, GWA studies have been used to investigate common and complex traits such as coronary artery disease [65,66], atrial fibrillation [67], prolonged QT interval, and SCD [68,69]. Following on from the discovery that common polymorphisms in the 5′ regulatory region of NOS1AP, encoding the protein Capon, modulate QTc, investigators are now examining the role of this set of variants in mediating SCD susceptibility in the NHLBI's ARIC (athereoscelerosis risk in communities) and CHS (cardiovascular health study-total enrollment >20,000), longitudinal studies.…”
Section: Current and Future Directionsmentioning
confidence: 99%